Work Life Balance of Career Oriented Women Employees - Rewathy, K. (International Research Conference on Gender Studies, Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura, 2023)
Gender equality and equity are currently being debated in a variety of contexts. Because of the standard of living and economic stability, both men and women are required to work in the majority of developing countries. Aside from gender-based discrimination and violence in the workplace and at home, women encounter problems and challenges in achieving their goals. Due to the lack of time, limited attention to the family, continuous work at home resulting in greater internal conflict within the family. The consequences lead the career oriented women undergo stress and unpleasant and peace less family life. The aim of the study is to examine various factors which be obstacles for the successful career opportunities for women. Purposive sampling method was chosen to interview twenty-five married women employees from different fields to obtain their information. Working women feel stressed both at workplace and households due to the major factors such as; unfriendly working environment, unlimited deadlines at work, child care, lack of time management, maintaining the social values and norms, etc. Ultimately the findings of the study emphasize the need of women empowerment workshops, counselling, and supportive systems for the women employees who are undergone by stress and anxiety. Furthermore, the construction of a supportive framework at the organizational level will result in more successful career-oriented women.
Keywords: Equality; Gender; Employee; Work-life balance; Women